2013
DOI: 10.5101/nbe.v4i3.p65-71
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal/Solvothermal Synthesis of Graphene Quantum Dots and Their Biological Applications

Abstract: Graphene quantum dots (GQDs), as a new class of zero dimensional fluorescent carbon material, have been used in physical, chemical and biological aspects for many interesting properties, such as low toxicity, excellent solubility, high chemical stability, and good surface activity. As a green synthetic method, hydrothermal/solvothermal technology has been applied to effectively control characteristics of GQDs. In this review, we summarize recent work on the hydrothermal/solvothermal synthesis of GQDs and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Since then, many studies concerning C-dots have been reported [2-4]. C-dots have attracted much attention due to their well-defined, nearly isotropic shapes together with their ultrafine dimensions and tunable surface functionalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, many studies concerning C-dots have been reported [2-4]. C-dots have attracted much attention due to their well-defined, nearly isotropic shapes together with their ultrafine dimensions and tunable surface functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dots (C-dots) are a new member of the carbon nanomaterial family after C 60 , carbon nanotubes, and graphene and were firstly discovered by accident when researchers were trying to purify single-walled carbon nanotubes (SWCNTs) fabricated by arc discharge methods [ 1 ]. Since then, many studies concerning C-dots have been reported [ 2 - 4 ]. C-dots have attracted much attention due to their well-defined, nearly isotropic shapes together with their ultrafine dimensions and tunable surface functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature plays a major part in the GQD texture in this process. Poorly ordered GQDs are synthesized at low temperature, and high crystallinity of GQDs is obtained at high temperatures 92 . The hydrothermal treatment of glucose can prepare boron‐doped GQD (BGQD) in the presence of boric acid, which has high electrocatalytic activity than undoped GQDs 93 …”
Section: Synthesis Methodsmentioning
confidence: 99%
“…The unique structure and property characteristics of GQDs make them attractive for bioimaging. Although tremendous progress has been achieved and a number of review articles on the synthesis, property and applications of GQDs in the fields of biosensing [19,36,37,41], drug delivery and photodynamic therapy [35,[42][43][44], energy-rated (photovoltaic devices, fuel cells, light-emitting diodes, catalysis and photocatalysis, etc.) [24,28,[45][46][47] and environmental monitoring [48][49][50] summarized, a focused overview on design and synthesis of GQDs for bioimaging is still missing.…”
Section: Introductionmentioning
confidence: 99%